Cervical cancer screening utilization and associated factors among women of 30–65 years in Girar Jarsoo district North shoa, Ethiopia, 2021 - Adugna Alemu Desta; Zerfu Mulaw Endale; Mastewal Belayneh Aklil (Clinical Epidemiology and Global Health, 2022)
Background: Cervical cancer screening is the method of early detection of cervical cancer before occurrence to decrease mortality and morbidity of the women. When women screened at least once in their lifetime for cervical cancer, their risk of cancer could be decreased by 25–36%. Despite this advantage the coverage of cervical cancer screening remains below 2% across country level. Therefore, this study aimed to assess cervical cancer screening utilization and associated factors among women 30–65 years in north shoa Ethiopia. Method: Community-based cross-sectional study was conducted using stratified cluster sampling technique among 855 women in March 2021. Data were collected using pretested and semi-structured interviewer administered questionnaire. Adjusted odds ratio with a 95% confidence interval was used to report the association between predictors and the outcome variable. Result: Cervical cancer screening utilization was found to be 21.2% (95% CI = 18.5–23.9).Being HIV positive [AOR = 16.49 (95% CI: 9.20–29.54)], knowing someone who had ever been screened for cervical cancer [AOR = 5.46 (95% CI: 2.53–11.79)], having good knowledge about cervical cancer screening [AOR = 3.8 (95% CI: 2.21–6.56)], women found in fourth quintile wealth index [AOR = 3.31 (95% CI: 1.13–9.70)] and having low perceived barriers for cervical cancer screening [AOR = 2.58 (95% CI: 1.43–4.64] were found to be significantly associated with cervical cancer screening utilization. Conclusion: The study revealed the utilization of cervical cancer screening among women 30–65 years is low. Health education program and other multi-disciplinary approaches should be done to increase cervical cancer screening utilization.